2023
DOI: 10.1017/s1047951122004280
|View full text |Cite
|
Sign up to set email alerts
|

Reintervention and mortality risk after total anomalous pulmonary venous connection repair

Abstract: Background: Management of total anomalous pulmonary venous connections has been extensively studied to further improve outcomes. Our institution previously reported factors associated with mortality, recurrent obstruction, and reintervention. The study purpose was to revisit the cohort of patients and evaluate factors associated with reintervention, and mortality in early and late follow-up. Methods: A retrospective review at our institution identified 81 patients undergoing total anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Bando et al 35 identified an association between a hypoplastic PVC and recurrent PVO. Additionally, Beers et al 36 reported the presence of a single-ventricle or a postoperative confluence gradient greater than 2 mmHg were risk factors for reintervention, and Sengupta et al 37 reported PV residua, age less than 1 year, and preoperative PVO were associated with reintervention. The precise mechanism remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Bando et al 35 identified an association between a hypoplastic PVC and recurrent PVO. Additionally, Beers et al 36 reported the presence of a single-ventricle or a postoperative confluence gradient greater than 2 mmHg were risk factors for reintervention, and Sengupta et al 37 reported PV residua, age less than 1 year, and preoperative PVO were associated with reintervention. The precise mechanism remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%